Digital library of thesis / Chong Fong Fong - Chong , Fong Fong (2001)
Digital library of thesis is a web-based library system for submitting, storing and disseminating or theses electronically. This system is proposed to overcome the short comings of the traditional methods of storing and disseminating or printed thesis. Users can use this system to upload their theses in the electronic form to the server and the theses can be retrieved using the efficient search capabilities provided. Source codes can be stored in this system too. This system provides an efficient way or handling source codes by storing the source codes in the reusable components or object form. This is to promote the reusability of the source codes for development of similar projects in the future. A survey has been carried out to explore the issues surrounding the electronic publication or thesis and to examine the feasibility) of submission, storage and distribution or electronic theses and dissertations. The survey sampled the progress made at other universities in the direction or moving to electronic theses. It also detailed the features offered by other digital libraries. In addition, the justification of the methodology used throughout the development of digital library of thesis is explained. The digital library of thesis is web-based application, thus all communications are done via TCP/IP protocol. All process are initiated when the user starts the digital library of thesis where the connection to the web server as well as the database server is established.